Correlation Between Hypothyroidism During Pregnancy and Glucose and Lipid Metabolism in Pregnant Women and Its Influence on Pregnancy Outcome and Fetal Growth and Development - Xu, Da; Zhong, Haolin (Frontiers in Surgery, 2022)
Purpose: To observe the Correlation between hypothyroidism during pregnancy and glucose and lipid metabolism in pregnant women and its influence on pregnancy outcome and fetal growth and development. Methods: 152 patients with hypothyroidism during pregnancy in our hospital from June 2017 to June 2020 were selected as the observation group, and divided into overt hypothyroidism (OH) group, subclinical hypothyroidism (SCH) group and low T4 group. Another 60 pregnant women with normal antenatal examination and normal thyroid function were selected as the normal group. The glucose and lipid metabolism indexes of each group were compared. The pregnant women in OH group and SCH group were given levothyroxine intervention, and the pregnancy outcome and infant development of the two groups were compared. Results: The FBG and HbA1c, TG and LDL of OH group and SCH group were higher than low T4 group and normal group, and OH group was higher than SCH group (P<0.05). The incidence of premature delivery and PROM at term in hypothyroidism non-control group were higher than hypothyroidism control group (P<0.05). The MDI and PDI in hypothyroidism non-control group were lower than hypothyroidism control group (P<0.05). Conclusion: Pregnant women with hypothyroidism during pregnancy are more prone to glucose and lipid metabolism disorder, which increases the risk of premature delivery and PROM at term, and has certain influence on the intellectual development and psychomotor development of infants.